Combination of HDAC inhibition and cytokine enhances therapeutic HPV vaccine therapy - Jeffrey Schlom; James L Gulley; Caroline Jochems; Sofia R Gameiro; Wiem Lassoued; Daniel Burnett; Lisa K Poppe; Nicholas Roller; Miriam Marlene Medina-Enríquez; Katherine E Lothstein; Asma S Khelifa; Masaya Miyamoto (Journal for ImmunoTherapy of Cancer)
Background Human papillomavirus (HPV)-associated malignancies continue to present a major health concern despite the development of prophylactic vaccines. Standard therapies offer limited benefit to patients with advanced-stage disease. Despite improved outcomes with programmed cell death protein-1 (PD-1) targeted therapies, treatment resistance and modest response rates highlight a significant unmet need to develop novel therapies for these patients. PDS0101 (designated HPV vaccine) is a liposomal nanoparticle HPV16-specific therapeutic vaccine that has been shown to generate strong HPV-specific responses in preclinical and clinical studies. Here we assess the efficacy of this HPV vaccine in combination with the tumor-targeting immunocytokine NHS-IL12 (PDS01ADC), plus either αPD-1 or the class I histone deacetylase inhibitor Entinostat.Methods Mice bearing HPV16+, αPD-1 refractory TC-1 and mEER tumors were treated with HPV vaccine, NHS-IL12, and either αPD-1 or Entinostat to determine antitumor efficacy and survival benefits. A comprehensive analysis of the tumor microenvironment was performed using flow cytometry, multiplex immunofluorescence, chemokine and cytokine assessment, and single-cell RNA sequencing with T-cell receptor (TCR) enrichment.Results Combination of HPV vaccine and NHS-IL12 with either Entinostat or αPD-1 yielded significant antitumor activity and prolonged survival in αPD-1 refractory models of HPV16+ cancer, with superior activity employing Entinostat versus αPD-1 combination. Entinostat triple therapy increased overall and HPV16-specific tumor CD8+ T-cell infiltration with heightened cytotoxicity. TCR sequencing revealed a CD8+ T-cell clone unique to vaccine-treated cohorts, which displayed an enriched cytotoxic transcriptional profile with triple therapy. These effects were paralleled by strong differentiation of tumor-associated macrophages (TAMs) towards pro-inflammatory, antitumor M1-like cell states. Single-cell transcriptomic analysis indicated all three agents were required for highest modulation of both CD8+ T cells and TAMs conducive to tumor control. A biomarker signature reflecting the preclinical findings was found to be associated with improved survival in patients with HPV-associated malignancies.Conclusion Together, these findings provide a rationale for the combination of HPV vaccine, NHS-IL12, and Entinostat in the clinical setting for patients with HPV16-associated malignancies.